IN DEFENSE OF THE STANDARD PICTURE: WHAT THE STANDARD PICTURE EXPLAINS THAT THE MORAL IMPACT THEORY CANNOT. (March 2022) - Watson, Bill
ABSTRACT: How do legal texts determine legal content? A standard answer to this question—sometimes called "the standard picture"—is that legal texts communicate something and what they communicate is identical to legal content. Mark Greenberg criticizes the standard picture and offers in its place his own "moral impact theory." My goal here is to respond to Greenberg by showing how the standard picture better explains legal practice than the moral impact theory does. To that end, I first clarify certain aspects of the moral impact theory. I then critique the theory, focusing on its inability to explain (i) why practitioners reason about legal content as they do and (ii) why they agree on legal content as often as they do. Finally, I refine the standard picture and demonstrate how it explains what the moral impact theory cannot.